Studi Pengetahuan Orang Tua tentang Gawai dan Pemberian Gawai pada Anak Usia 9-12 Tahun - Anang Rusmianto; Kukuh Pambuka Putra (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Improved technological developments can be felt throughout societies that can have a positive and negative effect. A parent’s knowledge will make the decision to give the child in charge. The purpose of this research is to describe the knowledge of parents about the gawais and the provision of gawais in children aged 9-12 years. The type of research used is quantitative descriptive. The population is a parent of elementary school students from Negeri Wonorejo 2 subdistrict of Semarang district. The number of respondents was 83 randomly picked people (random sampling). Collection of research data using questionnaires that have been tested for validity and reusability. The results showed that 55.4% of respondents knew about the function of gawais and 42.2% of respondents gave the child a gawai. From respondents who give the device only 19.4% that gives the child restrictions. The use of gawais provided by respondents is for entertainment, communication and for child control.